Gender, labor, and prime-age adult mortality: evidence from South Africa - Yamauchi, Futoshi; Buthelezi, Thabani; Velia, Myriam (International Food Policy Research Institute, 2006)
This paper examines the impact of prime-age adult mortality on the transition from school to the labor market of adolescents and on decisions by female adults to participate in the labor force in South Africa. The analysis focuses on that period—1998–2004—when South Africa experienced excess mortality due to the HIV/AIDS epidemic. We find, first, that deaths of prime-age adults significantly increase both male and female adolescents’ labor force participation because they stop their schooling in order to help support their families. Female school enrollment may also decrease because girls are required to stay at home to take care of the sick. Therefore, the total negative impact on schooling is larger among female adolescents than among male adolescents. Second, we find that female adults tend to join the labor force following the death of prime-age adult males. This change could cause a decrease in the time they spend on housework and child rearing. Combined, these findings imply that excess mortality of prime-age adults disrupts human capital formation.